Durable Shoulder Pain Relief and Avoidance of Surgery Up To 5 Years Following 60-Day PNS Treatment - Kevin E. Vorenkamp; Gemayel Lee; Denise D. Lester; Chaitanya Konda; Steven P. Cohen; Nate D. Crosby; Joseph W. Boggs (Pain and Therapy)
Abstract Introduction Shoulder pain can be a chronic, disabling condition resulting in major procedures like surgery that are invasive, costly, and pose significant risks to patients. Minimally invasive interventions that provide durable relief can improve outcomes while enabling patients to avoid accruing additional healthcare costs. The present survey study evaluated durability of pain relief in a real-world shoulder pain population following percutaneous 60-day peripheral nerve stimulation (PNS) treatment. Methods A cross-sectional follow-up survey assessed follow-up outcomes among patients who received 60-day PNS for chronic shoulder pain. Outcomes included patient-reported percent pain relief, average and worst pain scores, and patient impression of change in quality of life, physical function, and sleep. Patients also reported other treatments and interventions used for their shoulder pain since the 60-day PNS treatment including changes in medication usage. Results Among 489 survey participants (mean follow-up 21 months, range 6–60), 83% (405/489) reported no subsequent radiofrequency ablation, permanent implant, or surgery following 60-day PNS. Within this subset, 87% reported ongoing improvement in at least one domain at follow-up, including 71% who maintained ≥ 50% pain relief, and more than half who reported much or very much improved quality of life (61%), physical function (57%), or sleep (57%). Among those using PNS seeking to avoid surgery (n = 265), 81% reported no subsequent surgery, with 77% of those patients maintaining ≥ 50% pain relief. Outcomes were consistent across follow-up durations and shoulder pain etiologies. Conclusions This real-world evidence demonstrates that a large majority of responders to 60-day PNS may experience durable shoulder pain relief and other improvements, with benefits demonstrated up to 5 years post treatment. The low rate of progression to subsequent interventions including surgery suggests potential for healthcare economic benefit, supporting 60-day PNS as both a clinically effective and potentially economically advantageous approach for appropriate patients.